Hyperthermic Oncology From Bench to Bedside 2016
DOI: 10.1007/978-981-10-0719-4_13
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle-Mediated Hyperthermia and Induction of Anti-Tumor Immune Responses

Abstract: Magnetic nanoparticle-mediated hyperthermia (MNHT) can heat tumor tissue to the desired temperature without damaging surrounding normal tissue. The MNHT system consists of targeting tumor with functional magnetic nanoparticles (MNPs) and then applying an external alternating magnetic field (AMF) to generate heat in the MNPs. Temperature in the tumor tissue is increased to above 43 C, which causes necrosis of cancer cells but does not damage surrounding normal tissue. Among available MNPs, magnetite has been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…This size is also considered to be in the range to achieve the better heating properties for magnetite/maghemite. 40 MNPs have been prepared by thermal decomposition to have a careful control of the particle size and size distribution (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This size is also considered to be in the range to achieve the better heating properties for magnetite/maghemite. 40 MNPs have been prepared by thermal decomposition to have a careful control of the particle size and size distribution (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…This diameter fulfills the requirements for in vivo experimentation, as it avoids fast renal clearance. This size is also considered to be in the range to achieve the better heating properties for magnetite/maghemite …”
Section: Resultsmentioning
confidence: 99%
“…it was also suggested that gold nanoparticles may replace conventional iodine based contrasting agents as these reagents display renal toxicity and fast excretion. Gold nanoparticles displayed excellent biocompatibility, enhanced stability and increased accumulation in computed tomography tumor imaging (Kobayashi et al, 2016). Ultrasound imaging is a clinical diagnostic tool extensively used due to interesting features such as being non-invasive, cost-effective and portable.…”
Section: Theranosticsmentioning
confidence: 99%
“…These parameters need to be optimized before the in vitro/in vivo and preclinical studies. Many trials were performed to optimize some or all of those factors using different methods of particle preparations [16,17]. Other work has been developed to enhance the particles dispersion and biocompatibility in biological solutions using thermal seed of alloys, iron oxides as colloidal mediators, and Ni-Cu nanoparticles [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Many trials were performed to optimize some or all of those factors using different methods of particle preparations [16,17]. Other work has been developed to enhance the particles dispersion and biocompatibility in biological solutions using thermal seed of alloys, iron oxides as colloidal mediators, and Ni-Cu nanoparticles [17][18][19][20][21][22][23]. Although there have been many works to optimize the heating power-related factors, nanoparticles still represent considerable technical challenges like the formation of clusters and agglomerates, which negatively affect the total output heating power [24,25].…”
Section: Introductionmentioning
confidence: 99%